Behaviour of ionospheric magnitudes of F2 region over Tucumán during a deep solar minimum and comparison with the IRI 2012 model predictions - Ezquer, Rodolfo Gerardo (2014)
In this paper we analyze the behaviour of the critical frequency of the F2 region of the ionosphere (foF2) and the height of the maximum density of free electrons in F2 region (hmF2) over Tucumán (26.9°S, 294.6°E), during the deep solar minimum occurred in 2008–2009. Data used were compared with those obtained at solar minimum observed in 1975–1976 In addition, we check the validity of the International Reference Ionosphere model (IRI), in the version 2012, to predict the maximum free electron density in the ionosphere (NmF2) above the mentioned station, for very low solar activity. The results show that: (a) Ionization was lowest for recent solar minimum. (b) The semmianual anomaly which are present in the behaviour of foF2 at times of increased solar activity, was not clearly observed during the period 2008–2009. This phenomenon could be related with the very low solar activity for that period, confirming the relationship of the amplitude of this anomaly with the solar activity reported by other authors. (c) In most cases, the values of hmF2 recorded in the deep solar minimum are lower than those observed in the period 1975–1976, suggesting a decrease in the height of the ionosphere in the course of time, which could be related to the greenhouse effect in the atmosphere and the anomalously low solar extreme-ultraviolet irradiance. (d) IRI predictions show significant deviations from the experimental values, indicating the need for improvements in the model.